實習教師之人際互動關係與教師信念關聯之研究 The Canonical Correlation between Interpersonal Relationships and Teacher Beliefs of Pre-service Teachers - 劉世雄 Liu, Shih-Hsiung (National Changhua University of Education, 2012)
本研究之目的在於瞭解實習教師在實習機構之人際互動關係與教師信念的表現，並進一步分析這兩個變項的關聯情形。研究者自編問卷，並進行信度與效度的處理，邀請師資培育之大學的實習教師填寫，有效問卷399 份。描述性統計與Friedman 等級差異分析顯示，實習教師在人際互動關係與教師信念之分層面因素具有高度的表現，其中，與輔導教師的互動關係最高，與行政主管教師的互動關係較低。另外，典型相關分析結果顯示，人際互動關係與教師信念透過兩個典型因素彼此有高度的關聯。而實習教師與輔導教師的互動關係愈好，他們的課程與教學之信念將更高。本研究建議師資培育工作者可以培養師資生與實習教師均衡、正向與他人良性互動的能力，也建議未來可進一步研究確認人際互動關係與教師信念之可能的因果關係。 The purposes of the study are to investigate the interpersonal relationships of pre-service teachers as well as teachers' beliefs in field experience courses, and to determine the canonical correlation between interpersonal relationships and teacher beliefs. A validated questionnaire with high reliability was used to collect data from 399 pre-service teachers. The analytical results reveal that the pre-service teachers had high interpersonal relationships and strong pedagogical beliefs. Among sub-variables of interpersonal relationships, the interaction with mentors is the highest level while the interaction with administrative faculties is the lowest level. Moreover, there are two canonical factors that indicate the high correlations between four sub-variables of interpersonal relationships and four sub-variables of teacher beliefs. Specifically, the more positive pre-service teachers have interaction with their mentors, the stronger they hold beliefs about curriculum and instruction. Therefore, per-service teachers' ability to build positive relationship with mentors is recommended to be equipped during teacher education. The future research can further explore a possible cause relationship between interpersonal relationships and pedagogical beliefs for pre-service teachers.